"I think we should all be singing from the same hymn sheet" – English and Swedish midwives' views of advising pregnant women about alcohol. (3rd September 2019) - Schölin, Lisa; Hughes, Karen; Bellis, Mark A.; Eriksson, Charli; Porcellato, Lorna
Abstract: Many countries have adopted abstinence guidelines for pregnant women, due to uncertainty around the risk of harm caused by small amounts of alcohol. There is a lack of research exploring frontline midwives' attitudes towards alcohol use during pregnancy and comparisons of practices in different countries. Sixteen semi-structured interviews were conducted with midwives working in Liverpool, England ( n = 7) and Örebro County, Sweden ( n = 9). Data were analysed inductively, using thematic analysis with thematic networks. The findings show that all midwives believed pregnant women should be advised not to consume any alcohol during pregnancy and there is a need to tailor their approach to the individual. A key concern among midwives in both countries was how to advise about alcohol exposure that occurs before the pregnancy is known to the woman. English midwives discussed the uncertainty around the risk of consuming small amounts of alcohol, whereas Swedish midwives believed any amount of alcohol was associated with risk. Discussing alcohol was viewed as part of the health professional's role, but routine questions for all women were perceived to aid discussions about alcohol. Future research should further explore the impact of wider social and political environment on midwives' attitudes around risks with prenatal alcohol use.